ASPARTATE AMINOTRANSFERASE AND GAMMA GLUTAMYL TRANSFERASE: INTRIGUING CLINICAL BIOMARKERS IN DISCRIMINATION OF HEPATIC LESION BETWEEN HEPATITIS C INFECTED PATIENTS AND HEALTHY CONTROLS - Biljana Ilkovska; Bisera Kotevska Trifunova; Maja Avramovska; Biljana Taleva; Stefan Talev; Kosta Sotiroski; Petar Avramovski (Sestre Milosrdnice University Hospital, Institute of Clinical Medical Research, 2023)
SUMMARY – Over 1.5 million new cases of chronic hepatitis C virus (HCV) infection occur each year, infecting an estimated 58 million people worldwide. We aimed to find differences in peripheral blood count, liver enzymes and degradation products between HCV infected and healthy controls, and their impact on detection of the disease and discrimination of the diseased from non-diseased subjects. We performed laboratory testing for peripheral blood count, alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma-glutamyl transferase (γ-GT) and biliru bin in 40 HCV patients and 40 healthy controls. There were statistically significant differences in leuko cytes (p=0.001), ALT (p<0.0001), AST (p<0.0001), ALP (p<0.0001), γ-GT (p<0.0001), total bilirubin (p<0.018) and indirect bilirubin (p<0.030) between the HCV infected and control groups. On multiple regression, the independent variables of HCV titer (p=0.5091), granulocytes (p=0.7061) and total biliru bin (p=0.2022) showed no impact on liver lesion estimated by a dependent variable of γ-GT. On logistic regression, only AST [p=0.0112, odds ratio (OR)1.2161, area under the curve (AUC) 0.887] and γ-GT (p=0.0283, OR 1.1041, AUC 0.815) showed a statistically significantly positive predicting value when discriminating healthy subjects and diseased patients. In conclusion, HCV titer, granulocytes and total bilirubin did not show a statistically significant impact on hepatic lesion expressed by γ-GT, whereas only AST and γ-GT showed a statistically significant positive predicting value to discriminate infected patients from healthy controls. Each unit increase in AST and γ-GT resulted in 21.6% and 10.4% higher possibility for possible HCV infection, respectively.
Keywords: Hepatitis C virus (HCV); Aspartate aminotransferase; Gamma-glutamyl transferase; HCV titer; Liver enzymes